PENGEMBANGAN AGRIBISNIS DAN PENGOLAHAN MENDUKUNG PENSEJAHTERAAN PETANI CABE MERAH - Rooganda Elizabeth (Universitas Galuh Ciamis, 2019)
The procurement of raw materials for the red chili processing industry, the majority still comes from traders / suppliers. Chili starts procurement, processing to obtain added value, until marketing should be able to anticipate the limitations of the rights of farmers / gapotan groups that are more burdened with obligations. This paper aims to examine and express the role and benefits of chilli in the processing of red chillies to the marketing of processed products, related to efforts to accelerate the development of processing and agribusiness industries to improve the welfare of red chilli farmers. The benefits of partnership for farmer groups are the existence of market certainty, and relatively stable profits. The benefit for partners is the certainty of obtaining raw materials in accordance with the required specifications. The partner still gives the opportunity to sell to the free market if the price is better. The partnership development perspective is still very open, among others due to: (a) both parties obtain mutually beneficial benefits; (b) demand for processed products increases along with population growth. processing business is the transfer of raw material into highly-processed processed products that are able to meet the high demands of quality and hygienic (GMP) processed product requirements, as well as closely related to the increase in income from the acquisition of product value that is expected to realize and prosper farmers and businessmen , able to create jobs and increase interest in young workers on agriculture. The importance of changing the old mindset and paradigm of agriculture through the empowerment and development of chillies in processing and red chili processed agribusiness products is expected to be able to power the development of industrialization and the economy in rural areas.